Advanced Nanostructured Coatings Based on Doped TiO2 for Various Applications - Gartner Mariuca; Szekeres Anna; Stroescu Hermine; Mitrea Daiana; Covei Maria; Gutzov Stoyan (Molecules, 2023)
For many years, TiO2-based materials and improving their properties in order to expand their application areas have been the focus of numerous research groups. Various innovative approaches have been proposed to improve the photocatalytic and gas-sensing properties of TiO2 nanostructures. In this review, we aim to synthesize the available information in the literature, paying special attention to the sol-gel technology, which is one of the most frequently used methods for TiO2 synthesis. The influence of dopants on the structural, morphological, optical, and electrical properties of TiO2 and the way to modify them in a controlled manner are briefly discussed. The role of shallow and/or deep energy levels within the TiO2 bandgap in the electron transport behavior of doped TiO2 is emphasized. Selected research on photocatalytic applications in water disinfection, wastewater treatment, and self-sterilizing coatings that contribute to improving the quality of human life and environmental preservation is highlighted. A survey of biosensors that are closely related to medical applications such as cancer detection, implantology, and osteogenesis is also provided. Finally, the pressing problems that need to be solved in view of the future development of TiO2-based nanostructures are listed.
Keywords: titanium dioxide; structure and properties; photocatalytic applications; gas sensors and biosensors